2019
DOI: 10.1016/j.ijbiomac.2019.06.204
|View full text |Cite
|
Sign up to set email alerts
|

Poly(lactic acid)/cellulose nanocrystal composites via the Pickering emulsion approach: Rheological, thermal and mechanical properties

Abstract: Cellulose nanocrystals (CNCs) were evenly dispersed into poly(lactic acid) (PLA) via the Pickering emulsion approach. The PLA/CNC composites prepared were studied by rheological, thermal as well as mechanical measurements. Changes in the rheological characteristics of the composites showed that CNC promoted the transition of the composites from fluid to solid-like behavior at high temperatures. The introduction of 5 wt% CNC improved the crystallinity of PLA considerably and increased the onset temperature of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 41 publications
(27 reference statements)
3
34
0
1
Order By: Relevance
“…Lactic acid is an important building block for the production of biodegradable polymers as poly(lactic acid) (PLA) which are among the most frequently used in medical sutures and devices, bioimplants and scaffolds in tissue engineering. [220][221][222][223][224][225] While the mechanical properties of PLA films and many related materials have been studied, [226][227][228][229][230][231][232][233][234][235][236][237][238][239] the mechanical properties of solid lactic acid are unknown.…”
Section: L-(+)-lactic Acidmentioning
confidence: 99%
“…Lactic acid is an important building block for the production of biodegradable polymers as poly(lactic acid) (PLA) which are among the most frequently used in medical sutures and devices, bioimplants and scaffolds in tissue engineering. [220][221][222][223][224][225] While the mechanical properties of PLA films and many related materials have been studied, [226][227][228][229][230][231][232][233][234][235][236][237][238][239] the mechanical properties of solid lactic acid are unknown.…”
Section: L-(+)-lactic Acidmentioning
confidence: 99%
“…[5,6] The long-term stability of emulsions is an es-sentialf actor in many industries, such as food storageo rc osmetic formulations. [7,8] However,t here are severalo ther applications for which the short-term stabilization of an emulsion or reversible adsorption of surfactant is the primaryc oncern,i ncluding emulsion polymerization, [9] oil recovery, [10] andi nterfacial catalysis for biphasic reactions. [11] Switching on and off of Pickering emulsions has been extensively studied at different pH values, [12] temperatures, [13] magnetic fields, [14] and in the presence of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that the irreversible adsorption of particles at the oil interface in Pickering emulsions is due to the formation of a densely packed particle layer at the oil/water interface, which prevents both emulsion flocculation and coalescence by inducing a steric barrier . The long‐term stability of emulsions is an essential factor in many industries, such as food storage or cosmetic formulations . However, there are several other applications for which the short‐term stabilization of an emulsion or reversible adsorption of surfactant is the primary concern, including emulsion polymerization, oil recovery, and interfacial catalysis for biphasic reactions .…”
Section: Introductionmentioning
confidence: 99%
“…Improvement in tensile modulus, tensile strength, flexural modulus, and flexural strength has also been achieved with HNT, [ 222–224 ] sepiolite, [ 225–227 ] CNC, [ 228–230 ] CNF, [ 209, 210, 231 ] CNT, [ 232–234 ] and graphene [ 169, 235–238 ] the improvement being dependent on the filler loading, the extent of dispersion of the filler particles and their interaction with the PLA matrix (achieved by means of surface modification of the nanofiller or by use of compatibilizer).…”
Section: Properties Of Pla Nanocompositesmentioning
confidence: 99%
“…Cao et al [ 222 ] reported a lowering of the thermal stability of PLA with the incorporation of HNTs. Improvement in thermal stability of PLA due to incorporation of nanoparticles has been reported studies on PLA/CNC, [ 230 ] PLA/CNT, [ 262 ] and PLA/EG [ 169 ] nanocomposites.…”
Section: Properties Of Pla Nanocompositesmentioning
confidence: 99%